PERBEDAAN KEMAMPUAN LITERASI NUMERASI MENGGUNAKAN MEDIA LKPD CETAK DAN E-LKPD DALAM PEMBELAJARAN PROBLEM BASED LEARNING - Keimas, Atirah; Untu, Zainuddin (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
This experimental study examines the differences in students' numeracy literacy skills between learning using printed LKPD and E-LKPD within the Problem-Based Learning (PBL) model among seventh-grade students at SMP Negeri 6 Samarinda during the 2024/2025 academic year. The research employed a post-test-only control group design, where the first experimental group received PBL using printed LKPD, while the second group was taught using E-LKPD. The sampling technique used was purposive sampling, with the sample selection based on a preliminary test on integer operations. The results of the one-way ANOVA test showed a significance value (Sig.) of 0.88, indicating no significant difference in the initial average scores between classes VII-C and VII-D. The research data consisted of students’ scores on an AKM-based numeracy literacy test. Descriptive analysis showed that the average score of the first experimental class was 40.15, while the second experimental class achieved an average score of 52.89. Furthermore, the independent sample t-test analysis yielded a significance value ≤ 0.05, indicating a statistically significant difference. Therefore, it can be concluded that there is a substantial difference in students’ numeracy literacy abilities between the use of printed LKPD and E-LKPD in PBL learning at SMP Negeri 6 Samarinda in the 2024/2025 academic year.